Pengaruh Tepung Daun Kenikir (Cosmos caudatus Kunth) terhadap Kualitas Fisik Telur Burung Puyuh (Cortunix cortunix Japonicum) yang Disimpan selama 1 Minggu di Suhu Ruang - Dedy Kurniawan; Hanung Dhidhik Arifin; Roisu Eny Mudawaroch (Universitas Muhammadiyah Purworejo, 2019)
The study aims to determine the potential of Cosmos caudatus Kunth leaf flour as feed ingredients to improve the physical quality of quail eggs (Cortunix cortunix Japonicum) which are stored for 1 week at room temperature. The study was carried out at the Integrated Animal Husbandry Laboratory of Muhammmadiyah University, Purworejo. 120 female quails were placed in 24 enclosures. The ingredients used are Cosmos caudatus Kunth leaf flour (TDK) and commercial quail feed. Seals were taken as many as 48 eggs. The treatments given were S0 (0%), S1 (5%), S2 (10%), S3 (15%), S4 (20%) and S5 (25%). The method uses a completely randomized design (CRD) with 6 treatments and 4 replications. The parameters taken were egg yolk color, egg white index value, egg yolk index value, white pH value, and egg yolk. The results showed that giving Cosmos caudatus Kunth leaf flour had no significant effect (P <0.05) on the yolk color score of 7.88; 7.50; 7,12; 7.25; 7.38 and 7.25. The index value of egg white did not significantly affect (P <0.05) of 0.037; 0.034; 0.037; 0.034; 0.033 and 0.029. Yolk index value had no significant effect (P <0.05) of 0.39; 0.43; 0.48; 0.45; 0.48 and 0.43. Egg yolk pH value had no significant effect (P <0.05) of 6.13; 5.50; 5.56; 5.56; 5.44 and 5.63. The pH value of egg white significantly affected (P> 0.05) with a value of 9.19; 8.81; 8.75; 9.25; 9.50 and 9.56. Supplementation with Cosmos caudatus Kunth up to a dose of 25% cannot improve the physical quality of quail eggs (Coturnix-coturnix Japonicum) which are stored for 1 week at room temperature. Further research on Cosmos caudatus Kunth leaf flour needs to be done.